High-emissivity negative ion-modified graphene heating carbon slurry and preparation method thereof

The low-layer graphene powder and tourmaline powder prepared by using the mechanical peeling method, combined with the environmentally friendly solvent divalent acid ester, were prepared to produce high-emissivity negative ion modified graphene heated carbon slurry, which solved the stability and environmental friendliness of the existing heated carbon slurry, and achieved high stability and excellent physiotherapy effects.

CN114096021BActive Publication Date: 2025-03-18ZHEJIANG XIWEI NANO TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202111448570.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-01
Publication Date
2025-03-18
Estimated Expiration
2041-12-01

AI Technical Summary

Technical Problem

The existing heat-generating carbon slurry has many problems in terms of stability, far-infrared emissivity, environmental friendliness, etc., and it is difficult to meet the requirements of long-term stable use and environmental protection.

Method used

Low-layer graphene powder was prepared as a conductive filler by mechanical peeling method, and tourmaline powder was added to the far-infrared emitting material, combined with environmentally friendly solvent divalent acid ester, and high-emissivity negative ion modified graphene heated carbon slurry was prepared.

Benefits of technology

It improves the stability and far-infrared emissivity of the heating carbon slurry, and uses environmentally friendly solvents to reduce production costs and meets environmental protection requirements.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high-emissivity negative ion-modified graphene heating carbon slurry and a preparation method thereof. The raw materials are composed of the following components by weight: 15% to 35% of a binder, 15% to 35% of a conductive filler, 3% to 5% of a far-infrared emitting material, 2% to 3% of an auxiliary agent, and the balance is a solvent. The conductive filler is composed of graphene powder, conductive graphite, conductive carbon black, carbon nanotubes, and silver nanomaterials; the far-infrared emitting material is composed of tourmaline, bamboo charcoal powder, and infrared emitting powder. The invention has a simple production process, high far-infrared emissivity, and good stability of the heating carbon slurry. The product can be widely used in the fields of floor heating, wall heating, heaters, physical therapy products, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a high-emissivity negative ion-modified graphene heating carbon slurry and a preparation method thereof. The heating carbon slurry can be widely used in floor heating films, wall heating, heating murals, epoxy resin heating plates, heating carpets, heating tatami, far-infrared heaters and far-infrared physiotherapy products, etc. Background Art

[0002] Electric heating, as a comfortable and clean way of heating, is considered to have a significant effect on environmental improvement and air pollution control. Graphene, as a new type of carbon material with a two-dimensional layer structure, has high conductivity and emissivity. The far infrared released after it is powered on and heated has a therapeutic effect on the human body. Its layer structure is also conducive to overlapping other conductive fillers and far-infrared emitting materials in the heating carbon paste, making the conductive path more complete and stable after forming, thereby improving the stability of the heating carbon paste. Far-infrared materials such as tourmaline can release negative ions and far-infrared, which can not only purify the air but also play a therapeutic and health-care role on the body.

[0003] At present, there are many reports on heating carbon paste, and there are many patents related to heating carbon paste:

[0004] 1) Patent application number 201710045389.5 discloses a graphene low-pressure heating coating and a preparation method thereof. However, the carbon slurry prepared by this method has poor aging resistance, a large power change rate after heating for a period of time, and cannot be used stably for a long time.

[0005] 2) Patent application number 201910281177.6 discloses a graphene heating slurry and a graphene heating film obtained by using the same and a preparation method thereof. The graphene heating slurry comprises the following raw materials in parts by weight: 10-25 parts of ball-milled graphene powder, 5-10 parts of solvent and 60-75 parts of heating carbon slurry. The graphene heating film comprises a base film and the graphene heating slurry described above. The heating carbon slurry is a far-infrared electrothermal ink. A large amount of solvents such as DMF will be used in the process of producing heating carbon slurry using the method, which is highly polluting, toxic and not environmentally friendly.

[0006] 3) Patent application number 201811626053.9 discloses a method for preparing an environmentally friendly graphene conductive carbon slurry and its application in a flexible heating film. The heating carbon slurry prepared by the method has poor fluidity, poor film-forming performance, and uneven thickness after film formation. Currently, the heating carbon slurry still has many problems in terms of stability, far-infrared emissivity, and environmental friendliness.

[0007] 4) Patent application number 201910069658.0 discloses a method for preparing high-efficiency graphene heating carbon slurry: dry-mix conductive carbon black, graphene powder, graphite and nickel-plated graphite powder to obtain conductive filler; stir dispersant, leveling agent, defoamer and organic solvent in a disperser to obtain solvent; knead the conductive filler and solvent, and then perform corresponding treatment to obtain the finished product. However, the product obtained by this method has poor adhesion on the substrate.

[0008] 5) Patent No. 202010745404.9 discloses a high-conductivity self-adhesive graphene low-pressure heating slurry and its preparation method and application; the raw materials are formulated by mass as follows: 20-40 parts of graphene, 30-50 parts of heating carbon slurry, 1-5 parts of resin, 5-15 parts of solvent A, 10-20 parts of dispersant, 5-10 parts of water-based cross-linking coupling agent, 2-6 parts of defoaming agent, 3-5 parts of anti-settling agent; wherein: the graphene is prepared by shear stripping. However, the heating carbon slurry prepared by this patented method has poor uniformity and fluidity and is not suitable for production applications. Summary of the invention

[0009] The technical problem to be solved by the present invention is to provide a high-emissivity negative ion-modified graphene heating carbon slurry with good stability.

[0010] In order to solve the above technical problems, the present invention provides a high-emissivity negative ion-modified graphene heating carbon slurry, the raw materials of which are composed of the following components by weight:

[0011] The binder is 15% to 35%, the conductive filler is 15% to 35%, the far-infrared emitting material is 3% to 5%, the auxiliary agent is 2% to 3%, and the balance is the solvent.

[0012] As an improvement of the high-emissivity negative ion-modified graphene heating carbon paste of the present invention:

[0013] The auxiliary agent is at least one of a dispersant, a defoamer and a leveling agent.

[0014] The binder is composed of 60% to 80% by weight of polyester resin A and 20% to 40% by weight of polyester resin B;

[0015] The polyester resin A is a low molecular weight polyester resin, and the polyester resin B is a high molecular weight, high viscosity unsaturated polyester resin.

[0016] The conductive filler is composed of the following components by weight: 5% to 10% graphene powder, 35% to 40% conductive graphite, 35% to 40% conductive carbon black, 5% to 10% carbon nanotubes, and 2% to 5% silver nanomaterials;

[0017] The graphene powder is a low-layer (≤10 layers) graphene powder prepared by mechanical exfoliation;

[0018] The far infrared emitting material is composed of the following components by weight: 40% to 50% of tourmaline, 30% to 40% of bamboo charcoal powder, and 10% to 20% of infrared emitting powder (spinel type nano infrared emitting powder).

[0019] The solvent is a dibasic acid ester (mixed dibasic acid ester), for example, two or three of dimethyl succinate, dimethyl glutarate, and dimethyl adipate.

[0020] As a further improvement of the high-emissivity negative ion-modified graphene heating carbon paste of the present invention:

[0021] The solvent was DBE.

[0022] The dispersant is a BYK series dispersant, the defoamer is a silicone defoamer, and the leveling agent is a BYK series leveling agent.

[0023] As a further improvement of the high-emissivity negative ion-modified graphene heating carbon paste of the present invention:

[0024] The additives are composed of BYK190 dispersant, silicone defoamer BYK019, and BYK346 leveling agent in a mass ratio of 2:1:1.

[0025] As a further improvement of the high-emissivity negative ion-modified graphene heating carbon paste of the present invention:

[0026] The raw materials are composed of the following components by weight: 20% binder, 15% conductive filler, 5% far-infrared emitting material, 58% solvent, and 2% additive;

[0027] The conductive filler is composed of the following components by mass: 9% graphene powder, 40% conductive graphite, 36% conductive carbon black, 10% carbon nanotubes, and 5% silver nanomaterials;

[0028] The far infrared emitting material is composed of the following components by mass: 45% of tourmaline, 40% of bamboo charcoal powder, and 15% of infrared emitting powder (spinel type nano infrared emitting powder);

[0029] The binder is composed of polyester resin A and polyester resin B, with a weight ratio of polyester resin A to polyester resin B of 3:1;

[0030] The additives consist of BYK190 dispersant, silicone defoamer BYK019, and BYK346 leveling agent in a mass ratio of 2:1:1;

[0031] The solvent was DBE.

[0032] The present invention also provides a method for preparing the above-mentioned high-emissivity negative ion-modified graphene exothermic carbon slurry, comprising the following steps:

[0033] 1) The binder is evenly dissolved:

[0034] The binder and the solvent (dibasic acid ester solvent) are mixed, and heated and stirred in a reaction kettle until the binder is fully dissolved and mixed uniformly; thus, a binder containing the solvent is obtained;

[0035] 2) Conductive filler is evenly mixed:

[0036] The conductive filler is placed in a ball mill and ball-milled until the mixed powder is uniformly mixed;

[0037] 3) Even mixing of far infrared emitting materials:

[0038] The far-infrared emitting material is placed in a ball mill and ball-milled until the mixed powder is uniformly mixed;

[0039] 4) Preparation of heating carbon slurry:

[0040] The binder containing a solvent, a conductive filler, a far-infrared emitting material and an auxiliary agent are placed in a disperser and stirred and mixed. After stirring evenly, the mixture is taken out and placed in a three-roll grinder for full grinding to prepare a negative ion-modified graphene heating carbon slurry with high emissivity.

[0041] The performance index of the heating carbon paste in the present invention is mainly based on the aging performance data of the final product. After testing, the power change rate of the heating carbon paste provided by the present invention after accelerated aging test is less than 5%, which is much less than the 10% required by the industry standard JG / T286-2010, and is also better than most similar products on the market.

[0042] Compared with the existing similar technologies, the present invention has the following technical advantages: low-layer graphene powder is obtained by mechanical exfoliation as a raw material component, with intact structure, high far-infrared emissivity and relatively low cost; tourmaline powder added to the far-infrared emitting material can release negative ions after heating, and the far-infrared therapy effect is better; environmentally friendly solvent divalent acid ester is used as the main solvent of the heating carbon slurry, which can reduce production costs and is environmentally friendly, meets national policy requirements, and is suitable for large-scale industrial production.

[0043] The heating carbon paste of the present invention uses graphene, carbon nanotubes, conductive graphite, etc. as conductive fillers, and tourmaline, bamboo charcoal, etc. as far-infrared emitting materials, which have great advantages over traditional heating methods: 1) High stability: two binders with different molecular weights are used for blending and modification to improve the aging resistance of the binder. High-quality flake graphene is used as a conductive filler, which can better overlap other conductive fillers and improve product stability. 2) Excellent physiotherapy effect: graphene, bamboo charcoal, etc. have a very high emissivity, and the far infrared rays released by them can play a physiotherapy role on the human body. Tourmaline can release negative ions and far infrared rays, which can not only purify the air but also play a physiotherapy role on the human body. Environmental requirements and people's requirements for the quality of life have made environmentally friendly heating carbon paste with physiotherapy effects have broad market prospects. 3) Use electrical energy as energy to replace the traditional heating method using coal as energy. It also has excellent physiotherapy effects, simple production process, and high far-infrared emissivity. The product can be widely used in the fields of floor heating, wall heating, heaters, physiotherapy products, etc.

[0044] In summary, the preparation method of the present invention is simple, the resulting heating carbon slurry has good stability, and contains far-infrared negative ion emitting materials such as graphene and tourmaline. When heating, it can release far-infrared rays and negative ions at the same time, and has significant therapeutic effects. DETAILED DESCRIPTION

[0045] The present invention is further described in detail below through specific implementation. It should be noted that the following implementation is limited to the present invention, but is not intended to limit the scope of implementation of the present invention.

[0046] In the following cases, the stirring speed is 800-1500r / min.

[0047] In the present invention, all the components can be obtained in conventional commercial forms.

[0048] Environmentally friendly solvent divalent esters, for example, DBE solvent produced by Guangzhou Honghai Chemical.

[0049] The polyester resin A is a low molecular weight polyester resin (molecular weight is about 5000), for example, a polyester resin for coatings produced by Jining Sanshi Biotechnology Co., Ltd. can be selected;

[0050] The polyester resin B is an unsaturated polyester resin with high molecular weight and high viscosity (molecular weight is about 28,000, and the viscosity of the polyester resin B after being dissolved with a divalent acid ester is about 50,000 cps). For example, the ES300 resin produced by SK Company of South Korea can be selected;

[0051] The graphene powder has a powder layer number of ≤10 layers, for example, the general-purpose graphene powder produced by Ningbo Moxi Technology Co., Ltd. can be selected;

[0052] The particle size of conductive graphite is ≤0.02mm, for example, 1000 mesh conductive graphite produced by Qingdao Dongkai Graphite Co., Ltd. can be selected;

[0053] The diameter of the conductive carbon black particles is ≤60nm, for example, 3050B conductive carbon black produced by Mitsubishi Corporation of Japan can be selected;

[0054] The carbon nanotubes are multi-walled carbon tubes, for example, NC7000 carbon nanotubes produced by Beijing Tanyang Technology Co., Ltd. can be used;

[0055] The silver nanomaterial is a powder with a diameter of less than 50 nm, for example, the PT-AG-50 silver nanomaterial produced by Shanghai Pantian Powder Material Company can be used;

[0056] The tourmaline powder should be above 1000 mesh, for example, the AD00012 tourmaline produced by Ruixin Mineral Powder Company can be used;

[0057] The bamboo charcoal powder should be of 1000 mesh or above, for example, the 3000 mesh bamboo charcoal powder produced by Gaoliang Technology Company can be used;

[0058] The spinel nano-infrared emission powder is a 300-mesh spinel powder, for example, the 300-mesh spinel nano-infrared emission powder produced by Jingfeng Wear-resistant Materials Co., Ltd. can be used;

[0059] The organosilicon defoamer, for example, BYK019 organosilicon defoamer produced by BYK Company can be selected.

[0060] Example 1: A high-emissivity negative ion-modified graphene heating carbon paste, wherein the graphene powder content in the conductive filler is 5%, and the far-infrared emitting material content in the heating carbon paste is 3%:

[0061] The raw materials are composed of the following components in terms of mass content: 20% of a binder, 15% of a conductive filler, 3% of a far-infrared emitting material, 60% of a solvent, and 2% of an auxiliary agent.

[0062] The 2% additive is composed of BYK190 dispersant accounting for 1% of the total raw material, BYK019 organosilicon defoamer accounting for 0.5% of the total raw material, and BYK346 leveling agent accounting for 0.5% of the total raw material; that is, the mass ratio of BYK190 dispersant, organosilicon defoamer BYK019, and BYK346 leveling agent is 2:1:1.

[0063] The adhesive is composed of polyester resin A and polyester resin B, with the ratio of polyester resin A to polyester resin B being 3:1.

[0064] The conductive filler is composed of the following components in terms of mass content: 5% graphene powder, 40% conductive graphite, 40% conductive carbon black, 10% carbon nanotubes, and 5% silver nanomaterials.

[0065] The far-infrared emitting material is composed of the following components by mass: 50% of tourmaline, 40% of bamboo charcoal powder, and 10% of spinel type nano infrared emitting powder.

[0066] The solvent was DBE.

[0067] The preparation method comprises the following steps:

[0068] (1) Preparation of solvent-containing binder modification:

[0069] According to the raw material ratio, the binder (polyester resin A and polyester resin B) and DBE solvent were mixed and placed in a heated stirring reactor to dissolve. The heating temperature was 80° C. and the mixture was stirred for 3 hours until the mixture was uniform.

[0070] (2) Preparation of conductive filler:

[0071] 5% of graphene powder, 40% of conductive graphite, 40% of conductive carbon black, 10% of carbon nanotubes and 5% of silver nanomaterial are mixed together, the mixed powder is placed in a ball mill and ball milled until the mixed powder is uniformly mixed, and the mixed powder is passed through a 300-mesh sieve to obtain a conductive filler.

[0072] (3) Preparation of far-infrared emitting materials:

[0073] 50% of tourmaline, 40% of bamboo charcoal powder and 10% of spinel nano infrared emission powder are mixed together, the mixed powder is placed in a ball mill and ball milled until the mixed powder is uniformly mixed, and the mixed powder is passed through a 300-mesh sieve to obtain a far-infrared emission material.

[0074] (4) Preparation of heating carbon slurry:

[0075] According to the raw material ratio, the above-mentioned solvent-containing binder, conductive filler, far-infrared emitting material and additives are placed in a disperser and evenly stirred and mixed at a speed of 1000r / min for 30 minutes. After stirring evenly, the mixture is taken out and placed in a three-roll grinder for thorough grinding 5 times. After uniform grinding, high-emissivity negative ion-modified graphene heating carbon slurry can be obtained.

[0076] Experiment 1: The high emissivity negative ion modified graphene heating carbon slurry obtained in Example 1 was formed into a film according to the requirements of the low-temperature radiation electric heating film industry standard JG / T286-2010, and the power change rate was detected:

[0077] First, the heating carbon paste is modulated in an appropriate proportion according to the power required by the product, and then coated on substrates such as PET and PI by screen printing, gravure printing, etc. Dry at 120°C, print silver paste electrodes at both ends after drying, and make the heating film after the electrodes are dried. The heating film is powered on and tested at 1.35 times the rated voltage for 360 hours, and the power change rate before and after the test is compared. According to the requirements of the national standard GB / T7287-2008 test method for infrared radiation heaters, the normal total emissivity is measured after film formation, that is, the specific parameters of the heating film after power is turned on are tested using professional equipment.

[0078] The final result is:

[0079] The power change rate of the heat-generating carbon paste prepared in Example 1 after accelerated aging test is 3%, and the normal total emissivity after film formation is measured to be 0.87.

[0080] Example 2: A high-emissivity negative ion-modified graphene heating carbon slurry,

[0081] The raw materials are composed of the following components: 20% of a binder, 15% of a conductive filler, 4% of a far-infrared emitting material, 59% of a solvent, and 2% of an auxiliary agent.

[0082] The conductive filler is composed of the following components in terms of mass content: 6% of graphene powder, 40% of conductive graphite, 39% of conductive carbon black, 10% of carbon nanotubes, and 5% of silver nanomaterials.

[0083] The far-infrared emitting material is composed of the following components by mass: 50% of tourmaline, 35% of bamboo charcoal powder, and 15% of spinel type nano infrared emitting powder.

[0084] The rest of the contents (including the preparation method) are the same as those in Example 1.

[0085] The high-emissivity negative ion-modified graphene heating carbon paste prepared in Example 2 was tested according to the method described in Experiment 1 above, and the results obtained were:

[0086] The power change rate of the heat-generating carbon paste after accelerated aging test is 4%, and the normal total emissivity after film formation is measured to be 0.88.

[0087] Example 3: A high-emissivity negative ion-modified graphene heating carbon slurry,

[0088] The raw materials are composed of the following components: 20% of a binder, 15% of a conductive filler, 5% of a far-infrared emitting material, 58% of a solvent, and 2% of an auxiliary agent.

[0089] The conductive filler is composed of the following components in terms of mass content: 7% graphene powder, 40% conductive graphite, 38% conductive carbon black, 10% carbon nanotubes, and 5% silver nanomaterials.

[0090] The far-infrared emitting material is composed of the following components by mass: 40% of tourmaline, 40% of bamboo charcoal powder, and 20% of spinel type nano infrared emitting powder.

[0091] The rest of the contents (including the preparation method) are the same as those in Example 1.

[0092] The high-emissivity negative ion-modified graphene heating carbon paste prepared in Example 3 was tested according to the method described in Experiment 1 above, and the results obtained were:

[0093] The power change rate of the heat-generating carbon paste after accelerated aging test was 3.5%, and the normal total emissivity after film formation was measured to be 0.89.

[0094] Example 4: A high-emissivity negative ion-modified graphene heating carbon slurry,

[0095] The raw materials are composed of the following components: 20% of a binder, 15% of a conductive filler, 5% of a far-infrared emitting material, 58% of a solvent, and 2% of an auxiliary agent.

[0096] The conductive filler is composed of the following components in terms of mass content: 8% graphene powder, 40% conductive graphite, 37% conductive carbon black, 10% carbon nanotubes, and 5% silver nanomaterials.

[0097] The far-infrared emitting material is composed of the following components by mass: 45% of tourmaline, 35% of bamboo charcoal powder, and 20% of spinel-type nano-infrared emitting powder.

[0098] The rest of the contents (including the preparation method) are the same as those in Example 1.

[0099] The high-emissivity negative ion-modified graphene heating carbon paste prepared in Example 4 was tested according to the method described in Experiment 1 above, and the results obtained were:

[0100] The power change rate of the heat-generating carbon paste after accelerated aging test is 5%, and the normal total emissivity after film formation is measured to be 0.89.

[0101] Example 5: A high-emissivity negative ion-modified graphene heating carbon slurry,

[0102] The raw materials are composed of the following components: 20% of a binder, 15% of a conductive filler, 5% of a far-infrared emitting material, 58% of a solvent, and 2% of an auxiliary agent.

[0103] The conductive filler is composed of the following components in terms of mass content: 9% of graphene powder, 40% of conductive graphite, 36% of conductive carbon black, 10% of carbon nanotubes, and 5% of silver nanomaterials.

[0104] The far-infrared emitting material is composed of the following components by mass: 45% of tourmaline, 40% of bamboo charcoal powder, and 15% of spinel-type nano-infrared emitting powder.

[0105] The rest of the contents (including the preparation method) are the same as those in Example 1.

[0106] The high-emissivity negative ion-modified graphene heating carbon paste prepared in Example 5 was tested according to the method described in Experiment 1 above, and the results obtained were:

[0107] The power change rate of the heat-generating carbon paste after accelerated aging test is 3.5%, and the normal total emissivity after film formation is measured to be 0.90.

[0108] Example 6: A high-emissivity negative ion-modified graphene heating carbon slurry,

[0109] The raw materials are composed of the following components: 20% of a binder, 15% of a conductive filler, 5% of a far-infrared emitting material, 58% of a solvent, and 2% of an auxiliary agent.

[0110] The conductive filler is composed of the following components in terms of mass content: 10% of graphene powder, 40% of conductive graphite, 35% of conductive carbon black, 10% of carbon nanotubes, and 5% of silver nanomaterials.

[0111] The far-infrared emitting material is composed of the following components by mass: 50% of tourmaline, 40% of bamboo charcoal powder and 10% of spinel type nano infrared emitting powder.

[0112] The rest of the contents (including the preparation method) are the same as those in Example 1.

[0113] The high-emissivity negative ion-modified graphene heating carbon paste prepared in Example 6 was tested according to the method described in Experiment 1 above, and the results obtained were:

[0114] The power change rate of the heat-generating carbon paste after accelerated aging test is 5%, and the normal total emissivity after film formation is measured to be 0.90.

[0115] Comparative Example 1-1: The binder in Example 5 is changed to consist only of polyester resin A, the total amount remains unchanged, and the rest is the same as Example 5.

[0116] Comparative Example 1-2: The binder in Example 5 is changed to consist only of polyester resin B, the total amount remains unchanged, and the rest is the same as Example 5.

[0117] Comparative Example 1-3: The ratio of "polyester resin A: polyester resin B" in the binder of Example 5 was changed from 3:1 to 1:1, and the rest was the same as Example 5.

[0118] Comparative Examples 1-4: The binder in Example 5 is replaced with polyurethane resin, the dosage remains unchanged, and the rest is the same as Example 5.

[0119] Comparative Example 2-1: The conductive filler in Example 5 is changed to consist of "30% graphene powder, 40% conductive graphite, and 30% conductive carbon black", and the amount of the conductive filler remains unchanged. The rest is the same as Example 5.

[0120] Comparative Example 2-2: The conductive filler in Example 5 is changed to consist of "50% graphene powder, 30% conductive graphite, and 20% conductive carbon black", and the amount of the conductive filler remains unchanged. The rest is the same as Example 5.

[0121] Comparative Example 3-1: The 5% far-infrared emitting material in Example 5 is eliminated and replaced with 5% graphite powder, and the rest is the same as Example 5.

[0122] All the above comparative examples were tested according to the method described in Experiment 1, and the results are shown in Table 1 below:

[0123] Table 1

[0124] Group Aging power change rate (%) Normal total emissivity Example 5 3.5 0.90 Comparative Example 1-1 8.7 0.90 Comparative Example 1-2 10.6 0.90 Comparative Examples 1-3 6.5 0.90 Comparative Examples 1-4 8.3 0.90 Comparative Example 2-1 5.9 0.88 Comparative Example 2-2 6.3 0.88 Comparative Example 3-1 3.8 0.86

[0125] Finally, it should be noted that the above examples are only some specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and there are many variations. All variations that can be directly derived or associated with the content disclosed by a person skilled in the art should be considered as the protection scope of the present invention.

Claims

1. High emissivity negative ion modified graphene heating carbon paste, characterized by The raw material consists of the following ingredients in weight content: Binder 15% to 35%, conductive filler 15% to 35%, far-infrared emitting material 3% to 5%, auxiliary agent 2% to 3%, and the balance is solvent; The conductive filler is composed of the following components by weight: 5% to 10% graphene powder, 35% to 40% conductive graphite, 35% to 40% conductive carbon black, 5% to 10% carbon nanotubes, and 2% to 5% silver nanoparticles; The far-infrared emission material is composed of the following components by weight: 40% to 50% of tourmaline, 30% to 40% of bamboo charcoal powder, and 10% to 20% of infrared emission powder; The binder is composed of 60% to 80% by weight of polyester resin A and 20% to 40% by weight of polyester resin B, wherein the polyester resin A is a low molecular weight polyester resin with a molecular weight of 5000, and the polyester resin B is ES300 resin; The auxiliary agent is at least one of a dispersant, a defoamer, and a leveling agent; The solvent is a dibasic acid ester.

2. The high-emissivity negative ion-modified graphene heating carbon slurry according to claim 1, characterized in that: The solvent was DBE.

3. The high-emissivity negative ion-modified graphene heating carbon slurry according to claim 2, characterized in that: The dispersant is a BYK series dispersant, the defoamer is a silicone defoamer, and the leveling agent is a BYK series leveling agent.

4. The high-emissivity negative ion-modified graphene heating carbon slurry according to claim 3, characterized in that: The additives are composed of BYK190 dispersant, silicone defoamer BYK019, and BYK346 leveling agent in a mass ratio of 2:1:

1.

5. The high-emissivity negative ion-modified graphene heating carbon slurry according to claim 1, characterized in that: The raw materials are composed of the following components by weight: 20% binder, 15% conductive filler, 5% far-infrared emitting material, 58% solvent, and 2% additive; The conductive filler is composed of the following components by mass: 9% graphene powder, 40% conductive graphite, 36% conductive carbon black, 10% carbon nanotubes, and 5% silver nanomaterials; The far infrared emitting material is composed of the following components by mass: 45% of tourmaline, 40% of bamboo charcoal powder, and 15% of spinel type nano infrared emitting powder; The binder is composed of polyester resin A and polyester resin B, with a weight ratio of polyester resin A to polyester resin B of 3:1; The additives consist of BYK190 dispersant, silicone defoamer BYK019, and BYK346 leveling agent in a mass ratio of 2:1:1; The solvent was DBE.

6. The method for preparing the high-emissivity negative ion-modified graphene heating carbon slurry according to any one of claims 1 to 5, characterized in that The following steps are involved: 1) The binder is evenly dissolved: The binder and the solvent are mixed, and heated and stirred in a reaction kettle until the binder is fully dissolved and mixed uniformly to obtain a binder containing the solvent; 2) Conductive filler is evenly mixed: The conductive filler is placed in a ball mill and ball-milled until the mixed powder is uniformly mixed; 3) Far infrared emitting materials are evenly mixed: The far-infrared emitting material is placed in a ball mill and ball-milled until the mixed powder is uniformly mixed; 4) Preparation of heating carbon slurry: The binder containing a solvent, a conductive filler, a far-infrared emitting material and an auxiliary agent are placed in a disperser and stirred and mixed. After stirring evenly, the mixture is taken out and placed in a three-roll grinder for full grinding to prepare a high-emissivity negative ion-modified graphene heating carbon slurry.

Citation Information

Patent Citations

  • Graphene low-voltage exothermic paint and preparation method thereof

    CN106752878A

  • Method for preparing high-efficiency graphene heating carbon slurry

    CN109640410A

  • Preparation method of environment-friendly graphene conductive carbon paste and application of environment-friendly graphene conductive carbon paste to flexible heating film

    CN109817385A

  • Graphene heating slurry, graphene heating film prepared by using graphene heating slurry, and preparation method thereof

    CN109951902A

  • High-conductivity self-adhesive graphene low-voltage heating slurry and preparation method and application thereof

    CN111808453A